Ecomorphology of oral papillae and denticles of Zapteryx brevirostris (Chondrichthyes, Rhinobatidae) - Rangel, Bianca de Sousa; Ciena, Adriano Polican [UNESP]; Wosnick, Natascha; de Amorim, Alberto Ferreira; Kfoury Junior, José Roberto; Rici, Rose Eli Grassi (Springer Nature, 2016)
Elasmobranchs have an impressive range of highly specialized sensory systems shaped over 400 million years of evolution. The morphological analysis of oral papillae and denticle in elasmobranchs elucidates the biological role that these structures play during feeding and ventilation, bringing important descriptive information about ecological implications in an evolutionary context. The present study provides descriptions of the distribution patterns, histological characteristics and three-dimensional aspects of oral papillae and denticles in the lesser guitarfish Zapteryx brevirostris, through light microscopy and scanning electron microscopy. The presence of oral denticles in the oropharyngeal cavity suggests that this structure may have the following functions: protect against abrasion and parasites, increase the ability to grasp and hold prey and assist in reduction in hydrodynamic drag. The denticles in Z. brevirostris are similar to those found in pelagic sharks with forced ventilation (RAM). The structural conformity of denticles observed in the gill slits may facilitate water flow during prey grasp and food processing. This study supports the hypothesis that these structures may be an adaptive reflection shaped by feeding habits, capture strategies and processing prey.
Keywords: Feeding; Guitarfish; Oropharyngeal cavity; Tasting; Ventilation